DHX15 Inhibits Autophagy and the Proliferation of Hepatoma Cells - Zhao, Miaomiao; Ying, Lixiong; Wang, Rusha; Yao, Jiping; Zhu, Liming; Zheng, Min; Chen, Zhi; Yang, Zhenggang (Frontiers in Medicine, 2021)
Autophagy is a highly conserved process by which superfluous or harmful components in eukaryotic cells are degraded by autophagosomes. This cytoprotective mechanism is strongly related to various human diseases, such as cancer, autoimmune diseases, and diabetes. DEAH-box helicase 15 (DHX15), a member of the DEAH box family, is mainly involved in RNA splicing and ribosome maturation. Recently, DHX15 was identified as a tumour-related factor. Although both autophagy and DHX15 are involved in cellular metabolism and cancer progression, their exact relationship and mechanism remain elusive. In this study, we discovered a nonclassic function of DHX15 and identified DHX15 as a suppressive protein in autophagy for the first time. We further found that mTORC1 is involved in DHX15-mediated regulation of autophagy and that DHX15 inhibits proliferation of hepatocellular carcinoma (HCC) cells by suppressing autophagy. In conclusion, our study demonstrates a nonclassical function of DHX15 as a negative regulator of autophagy related to the mTORC1 pathway and reveals that DHX15-related autophagy dysfunction promotes HCC cell proliferation, indicating that DHX15 may be a target for liver cancer treatment.